2011
DOI: 10.1074/jbc.m110.192955
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Induces RNA Polymerase III-dependent Transcription through c-Jun by Co-regulating TATA-binding Protein (TBP) and Brf1 Expression

Abstract: Chronic alcohol consumption is associated with steatohepatitis and cirrhosis, enhancing the risk for hepatocellular carcinoma. RNA polymerase (pol) III transcribes a variety of small, untranslated RNAs, including tRNAs and 5S rRNAs, which determine the biosynthetic capacity of cells. Increased RNA pol III-dependent transcription, observed in transformed cells and human tumors, is required for oncogenic transformation. Given that alcohol consumption increases risk for liver cancer, we examined whether alcohol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
138
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(143 citation statements)
references
References 27 publications
4
138
1
Order By: Relevance
“…Protein concentrations of the resultant lysates were measured by the Bradford method using a Fluostar Omega spectrometer (Cell Biology Core Laboratory of University of Southern California Research Center for Liver Diseases, P30 DK048522). Lysates (50 μg of protein) of tissues or cells were separated by SDS/PAGE and subjected to western blot analysis as previously described (Zhong et al ., 2011, 2013b). Membranes were probed with specific antibodies against Brf1, ERα, and β‐actin as indicated.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Protein concentrations of the resultant lysates were measured by the Bradford method using a Fluostar Omega spectrometer (Cell Biology Core Laboratory of University of Southern California Research Center for Liver Diseases, P30 DK048522). Lysates (50 μg of protein) of tissues or cells were separated by SDS/PAGE and subjected to western blot analysis as previously described (Zhong et al ., 2011, 2013b). Membranes were probed with specific antibodies against Brf1, ERα, and β‐actin as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…tRNA and 5S rRNA control the translational and growth capacity of cells (Goodfellow et al ., 2006; White, 2004). Studies have indicated that oncogenic proteins, such as c‐Myc, c‐Jun, c‐Fos, and Ras, increase Pol III gene transcription (Goodfellow et al ., 2006; Johnson et al ., 2008; Zhang et al ., 2011, 2013; Zhong and Johnson, 2007; Zhong and Johnson, 2009; Zhong et al ., 2011). In contrast, tumor suppressors, such as BRCA1, p53, PTEN, and pRB, decrease transcription of these genes (Johnson et al ., 2008; White, 2004; Woiwode et al ., 2008; Zhong et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations